Bipartite fidelity for models with periodic boundary conditions. Issue 2 (4th February 2021) - Morin-Duchesne, Alexi; Parez, Gilles; Liénardy, Jean
Abstract: For a given statistical model, the bipartite fidelity F is computed from the overlap between the groundstate of a system of size N and the tensor product of the groundstates of the same model defined on two subsystems A and B, of respective sizes N A and N B with N = N A + N B . In this paper, we study F for critical lattice models in the case where the full system has periodic boundary conditions. We consider two possible choices of boundary conditions for the subsystems A and B, namely periodic and open. For these two cases, we derive the conformal field theory prediction for the leading terms in the 1/ N expansion of F, in a most general case that corresponds to the insertion of four and five fields, respectively. We provide lattice calculations of F, both exact and numerical, for two free-fermionic lattice models: the XX spin chain and the model of critical dense polymers. We study the asymptotic behaviour of the lattice results for these two models and find an agreement with the predictions of conformal field theory.